2004
DOI: 10.1016/j.jpainsymman.2004.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Study of unmet needs in symptomatic veterans with advanced cancer: incidence, independent predictors and unmet needs outcome model

Abstract: Veteran patients possess distinctive characteristics such as a higher mortality rate, lower socioeconomic status and poorer health status. We report the prevalence and predictors of unmet needs and examine the association between unmet needs and quality of life (QOL). Two hundred ninety-six male cancer patients who presented with distressing symptom(s) completed the following instruments: a 14-item multidimensional unmet needs questionnaire, Functional Assessment of Cancer Therapy (FACT-G), Memorial Symptom As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
76
3
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 29 publications
14
76
3
6
Order By: Relevance
“…In 46 studies, (part of) the aim of the study had been to determine the prevalence of pain in cancer patients. This had not been a primary goal in the other eight studies [11,13,49,65,71,73,75,82,84]. One study looked at unmet needs, one described the experiences of a palliative care programme, two compared usual care with intensive care, one was on the influence of demographic and disease specific variables on pain and one compared differences in symptoms between cancer and noncancer patients.…”
Section: General Characteristicsmentioning
confidence: 99%
“…In 46 studies, (part of) the aim of the study had been to determine the prevalence of pain in cancer patients. This had not been a primary goal in the other eight studies [11,13,49,65,71,73,75,82,84]. One study looked at unmet needs, one described the experiences of a palliative care programme, two compared usual care with intensive care, one was on the influence of demographic and disease specific variables on pain and one compared differences in symptoms between cancer and noncancer patients.…”
Section: General Characteristicsmentioning
confidence: 99%
“…[34][35][36] For instance, a study about the survivors of World Trade Center terrorist attacks reported that one-third of people who had posttraumatic stress disorder or depression experienced UMN.…”
Section: )mentioning
confidence: 99%
“…While oncological studies increasingly include both HRQoL and needs questionnaires [4][5][6][7][8][9][10][11][12][13], few studies have compared the two approaches and these comparisons have primarily involved correlational analysis alone [4; 7; 8; 11; 12].…”
Section: A Comparison Of the Fact-g And The Supportive Care Needs Surmentioning
confidence: 99%